Intercultural Mediation & Conflict Resolution - Boness, Christian M
Would you like to acquire intercultural competencies that would open new perspectives to you, and new options for action, and new options, especially in negotiations, and situations of conflict? This book gives information on procedures and processes of mediation in Western and intercultural contexts, and explains them. Readers come in contact with what is special about mediation, and working with conflict, in interaction between Germans and Africans. Finally, the authors place at readers' disposal introductory training methods, necessary for all who wish to work responsibly in intercultural contexts. The book's "constructivist" approach affords the perception of new aspects and perspectives of German-African realities, and of the current discussion on intercultural conflict-management